Toxicity Assessment of Cultured Cyanobacteria Toxin by Using Bioassay (Brine Shrimp, Artemia Salina), Thin Layer and High Performance Liquid Chromatography - Lai, Jia Rhou (Universiti Malaysia Sarawak, UNIMAS, 2011)
Cyanobacterial toxicity was both tested from the natural water samples and isolated cyanobacterial samples collected from aquaculture ponds in Indigenous Fisheries Research and Production Center (IFRPC) Tarat, Serian. Water quality parameters such as salinity, turbidity, dissolved oxygen, pH and temperature were taken. Anabaena sp. was isolated and mass cultured by using medium ASN3. The cells were harvested at their late exponential phase of growth. Crude extracts were obtained from natural samples and Anabaena sp. by using 95% methanol. Brine shrimp (Artemia salina) bioassay was carried out on Anabaena strain by using eight concentrations (2, 5, 10, 20, 30, 40, 50, 100 g/ml) in filtered seawater. Endpoint of the experiment was mortality of brine shrimp. LC50 value obtained was approximately 8.32 g/ml and lethality at 30 g/ml. Thinlayer chromatography (TLC) and high performance liquid chromatography (HPLC) were used for further examination of microcystin by using standard of microcystin-LR. Microcystin were not detected in all of the samples, however, other toxins such as neurotoxin are expected to be available based on the mortality of the brine shrimps, retention factor values in TLC and overlay of peaks at 5.0 minutes retention times shown in HPLC chromatogram.